Automatic synchronization of a feature model with direct editing based on cellular model. Issue 5 (29th July 2017) - Fu, Jun; Chen, Xiang; Gao, Shuming
ABSTRACT: As the de-facto standard in modern CAD systems, feature-based modeling is widely used in industry. Direct modeling, in contrast, is an emerging technology which allows users to promptly and directly edit B-rep models. To exert the powers of both technologies in a single design session and enable the communication between them, we propose a method that automatically converts direct modeling operations into feature model modification operations. We sequentially adopt three synchronization strategies - feature parameter modification, feature order adjustment and feature add/remove - to preserve the original design semantics of the feature model as much as possible. With a series of experiments, we demonstrate that the proposed method can fuse direct modeling and feature-based modeling in a natural and efficient way. GRAPHICAL ABSTRACT: